Perceptions of Spirituality and Spiritual Care in Religious Nurses. Issue 4 (October 2016) - Sanders, Lynne; Kopis, Sharon; Moen, Carolyn; Pobanz, Angela; Volk, Fred
Abstract : ABSTRACT: This study explored nurses' perceptions of how they provide spiritual care, the barriers to delivering spiritual care, and the adequacy of their education and training on spiritual care. Past and current students from a faith-based university nursing program completed an online survey ( N = 614). Participants reported varying definitions of spirituality and view spiritual care practices through a wide lens. The majority believed nurses do not receive sufficient spiritual education but reported they usually feel able to meet patients' spiritual needs. Time limitations were the most frequent obstacle to providing spiritual care. Abstract : Researchers explored religious nurses' perceptions of spiritual care, barriers, and the adequacy of their spiritual care education. The results provide evidence for better spiritual care training.